Capital structure and financial performance: Case study from Pakistan pharmaceutical sector - Muhammad Rehan; Süleyman Serdar Karaca; Jahanzaib Alvi (Financial Studies, 2020)
The main purpose of this research is to find out the relationship between capital structure and the firm's financial performance of the listed Pharmaceutical companies in the Pakistan Stock Exchange. A further specific objective is to find out the relation of debt-equity with gross profit, earning per share, and return on capital and return on equity. This research determines that Capital Structure is adversely linked with the profitability, it suggests that a decrease in the profitability of the organizations is due to an increase in debt capital & vice versa, further the results proclaims that capital is not dramatically significant and impacting, hence results in records that debt to equity is nothing to do with ROE, increasing or decrease in debt or equity financing would affect ROE.
Keywords: G32; 330; Return on Capital; Return on Equity; Debt to Equity; KSE-100 Index